(untitled) (Indian Journal of Public Health Research & Development, 2020)
Aim: Dentists could play an important role in tobacco cessation counseling. This study is conducted to assess dental professionals’ understanding of tobacco prevention and control methods. Material and Method: A descriptive cross sectional study was conducted in which a close-ended, self-administered 30 item-questionnaire was distributed among 130 interns at private dental institutions in Chennai. Demographic data, tobacco use status, attitudes toward cessation programs, perceived barriers and counseling procedure was filled by the surveyed subjects. Results: About 97.7% of the dental interns agreed their role in helping patients to quit smoking. Though 82.3% enquired all their patients regarding their smoking status, 86.9% of them feared improper follow up. Nearly 85.4% of the respondents believed that the counseling done is effective but only 32% anticipated successful intervention and 21% of them were very confident in conducting it. Conclusion: It was concluded that although dentists were aware of their obligations towards smoking cessation counseling for patients but certain factors like lack of time, confidence, ,training ,absence of reimbursement and fear of losing patients were the common barriers for the same. Expansion of armamentarium to include tobacco cessation counseling strategies in clinical practice must be adopted by all dental professionals.